"[It's] what you do after the mistake that counts": Positive employment credentials, criminal record stigma, and potential pathways of mediation. Issue 1 (12th September 2022) - Denver, Megan; DeWitt, Samuel E.
Abstract: The findings from prior research indicate that positive credentials, or documentation of prosocial accomplishments, can vary in strength and perceived value in mitigating aversions to hiring individuals with criminal records. In the current study, we examine why certain types of positive credentials may be more influential in reducing stigma than others. Using data from a nationwide survey of American adults (N = 3, 476), we combine a mediation analysis with content‐coding of open‐ended responses to identify key themes and patterns in decision processes. The results indicate the factors examined here—employee dependability, trustworthiness, recidivism risk, and workplace crime—explain a large proportion of the total effect across credentials and are the strongest for reference letters. Trustworthiness is the most influential mediator across credentials, whereas general recidivism risk is consistently the lowest. An analysis of open‐ended responses provides further context and insight into these patterns. Although policy strategies often target risk reduction on the employer's end, credentials that also relay information about skills, character, and the timeline of recent life events are especially influential.